Surface modification of mineral dust particles by sulphuric acid processing: implications for ice nucleation abilities - P. Reitz; C. Spindler; T. F. Mentel; L. Poulain; H. Wex; K. Mildenberger; D. Niedermeier; S. Hartmann; T. Clauss; F. Stratmann; R. C. Sullivan; P. J. DeMott; et al. (Atmospheric Chemistry and Physics, 2011)
The ability of coated mineral dust particles to act as ice nuclei (IN) was investigated at LACIS (Leipzig Aerosol Cloud Interaction Simulator) during the FROST1- and FROST2-campaigns (Freezing of dust). Sulphuric acid was condensed on the particles which afterwards were optionally humidified, treated with ammonia vapour and/or heat. By means of aerosol mass spectrometry we found evidence that processing of mineral dust particles with sulphuric acid leads to surface modifications of the particles. These surface modifications are most likely responsible for the observed reduction of the IN activation of the particles. The observed particle mass spectra suggest that different treatments lead to different chemical reactions on the particle surface. Possible chemical reaction pathways and products are suggested and the implications on the IN efficiency of the treated dust particles are discussed.